The political economy of conscription - Panu Poutvaara; Andreas Wagener (Center for Economic Studies and ifo Institute (CESifo), 2009)
Though in decline recently, military conscription is still a widely used mode of staffing armies. Since not many valid economic, social or military arguments in favor of the draft can be put forward, the question emerges why societies choose to rely on it. In this survey we explain the political allure of military conscription by its specific intra- and intergenerational incidence as a tax. From a public choice perspective, there is always a vast majority of people in favor of the introduction and maintenance of military draft, as compared to a professional army. Empirical evidence for this conclusion appears to be mixed, however. Political preferences with respect to conscription involve concerns about its unfairness and questionable record on social accounts. Special interests may also matter.
Keywords: H56; D72; 330; military draft; public choice; taxation; dynamic costs; fairness; Wehrdienst; Verteidigungshaushalt; Public Choice; Excess Burden; Gerechtigkeit